Combined Effects in Singular Elliptic Problems in Punctured Domain - Imed Bachar; Habib Mâagli; Hassan Eltayeb (Journal of Function Spaces)
The paper deals with nonlinear elliptic differential equations subject to some boundary value conditions in a regular bounded punctured domain. By means of properties of slowly regularly varying functions at zero and the Schauder fixed-point theorem, we establish the existence of a positive continuous solution for the suggested problem. Global estimates on such solution, which could blow up at the origin, are also obtained.